2015
DOI: 10.1371/journal.pone.0134038
|View full text |Cite
|
Sign up to set email alerts
|

Thinking Styles and Regret in Physicians

Abstract: BackgroundDecision-making relies on both analytical and emotional thinking. Cognitive reasoning styles (e.g. maximizing and satisficing tendencies) heavily influence analytical processes, while affective processes are often dependent on regret. The relationship between regret and cognitive reasoning styles has not been well studied in physicians, and is the focus of this paper.MethodsA regret questionnaire and 6 scales measuring individual differences in cognitive styles (maximizing-satisficing tendencies; ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 38 publications
0
41
0
Order By: Relevance
“…We found that worries/fear about overlooking a severe illness were quite dominant emotions in the GPs’ narrations, which related to rather categorical precautionary prescribing and hospitalization. From a psychological perspective, such “action rather than inaction”38 may compose a strategy to deal with uncertainty through avoiding unpleasant feelings and pondering after the decision is made 39,40. GPs may also experience “prescribing against the evidence,” such as prescribing antibiotics without proof of bacterial infection, as uncomfortable.…”
Section: Discussionmentioning
confidence: 99%
“…We found that worries/fear about overlooking a severe illness were quite dominant emotions in the GPs’ narrations, which related to rather categorical precautionary prescribing and hospitalization. From a psychological perspective, such “action rather than inaction”38 may compose a strategy to deal with uncertainty through avoiding unpleasant feelings and pondering after the decision is made 39,40. GPs may also experience “prescribing against the evidence,” such as prescribing antibiotics without proof of bacterial infection, as uncomfortable.…”
Section: Discussionmentioning
confidence: 99%
“…It is also a feat of effortful processing, since counterfactual thinking requires hypothetical simulation of possibilities—in other words, new mind processing. Thus, regret serves as a link between intuitive and effortful processes (Table ) providing mechanism for dual process rationality model . When regret is taken into account, “stubborn quest for diagnostic certainty” may not be irrational …”
Section: Descriptive Principles Of Decision‐making I: Dual Processingmentioning
confidence: 99%
“…In the setting of dual‐processing architecture, it is important to realize that regret, as a cognitive emotion, is characterized by a counterfactual reasoning process: It operates imagining “what if” scenarios—we regret when we compare the actual outcome to what might have happened, but did not . In this respect, regret serves as a link between intuitive and effortful processes, providing a mechanism for a dual‐process rationality model . The threshold model, which links the key features of clinical medicine: evidence with decision making, has also been formulated within a framework of dual‐processing theories .…”
Section: Overuse and Underuse Under Descriptive Theories Of Decision mentioning
confidence: 99%